Classic thrombophilic gene variants - Mannucci, Pier Mannuccio; Franchini, Massimo (Thrombosis and Haemostasis, 2015)
Thrombophilia is defined as a condition predisposing to the development of venous thromboembolism (VTE) on the basis of a hypercoagu-lable state. Over the past decades, great advances in the pathogenesis of VTE have been made and nowadays it is well established that a thrombophilic state may be associated with acquired and/or inherited factors. The rare loss-of-function mutations of the genes encoding natural anticoagulant proteins (i. e. protein C, protein S and antithrombin) and the more common gain-of-function polymorphisms factor V Leiden and prothrombin G20210A are the main genetic determinants of thrombophilia. In addition, non-O blood group has been consistently demonstrated to be the most frequent inherited marker of an increased risk of VTE. The mechanism role of these inherited thrombophilia markers will be discussed in this narrative review.
Keywords: Inherited thrombophilia; natural anticoagulants; factor V Leiden; prothrombin mutation; ABO blood group